Global urban monitoring and assessment through earth observation - Weng, Qihao (CRC Press/Taylor & Francis Group, 2014)
"Cities and towns are the original producers of many of the global environmental problems related to waste disposal, air and water pollution. There is a rapidly growing need for technologies that will enable monitoring of the world's natural resources and urban assets, and managing exposure to natural and man-made risks. The Group on Earth Observation calls for strengthening the cooperation and coordination among global observing systems and research programs. The book introduces this important international collaborative effort, reviews the current state of global urban remote sensing, and expands on future directions in the field."-- Provided by publisher.
Keywords: Urban geography -- Remote sensing -- International cooperation.; Land use, Urban -- Remote sensing -- International cooperation.; Environmental monitoring -- Remote sensing -- International cooperation.; Geographic information systems.; elektronické knihy; electronic books